2019
DOI: 10.5152/fnjn.2019.426870
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Guide Based Application Bundle on the Catheter-Related Infection

Abstract: Aim: Central venous catheters are used extensively in intensive care units but can sometimes lead to catheter related blood stream infections. This study was carried out to determine the effect of guidelinebased care bundle on possible catheter-related bloodstream infection in the application and care of central venous catheter in patients receiving follow-up and treatment in anesthesia intensive care unit. Method: The study is a retrospective and experimental one. The study population consisted of patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…They found that central line bundle programs were found to be effective in decreasing central line-associated bloodstream infection rates. In the same context, Süha and Karagözoğlu (2019) in their study about "The Effect of a Guide Based Application Bundle on the Catheter-Related Infection." It was found that the guideline-based care bundle is an effective and useful way to reduce CLABSI.…”
Section: Discussionmentioning
confidence: 99%
“…They found that central line bundle programs were found to be effective in decreasing central line-associated bloodstream infection rates. In the same context, Süha and Karagözoğlu (2019) in their study about "The Effect of a Guide Based Application Bundle on the Catheter-Related Infection." It was found that the guideline-based care bundle is an effective and useful way to reduce CLABSI.…”
Section: Discussionmentioning
confidence: 99%